Effect of body mass index on the wound infection and complications in patients with liver cancer: A meta‐analysis - Li, Yan‐Ping; Gan, Zhuo; Shi, Bing (International wound journal, 2024)
This study systematically evaluates the effect of body mass index on the occurrence of wound infections and complications in patients undergoing liver cancer surgery through a meta‐analysis. A computerized search was conducted, from database inception to October 2023, in PubMed, Embase, Google Scholar, Cochrane Library, China National Knowledge Infrastructure and Wanfang databases for studies related to the impact of body mass index on patients undergoing liver cancer surgery. Two researchers independently selected studies based on inclusion and exclusion criteria, extracted data, and assessed the quality. Data analysis was performed using Stata 17.0 software. A total of 8 studies, encompassing 21 030 liver cancer surgery patients, were included. The analysis revealed that patients with a higher body mass index had a significantly higher incidence of wound infection (odds ratio [OR] = 2.36, 95% confidence interval [CI]: 1.21–4.60, p = 0.012) and complications (OR = 1.58, 95% CI: 1.11–2.24, p = 0.011) compared to the control group. Additionally, the hospital stay for higher body mass index patients was longer than that for the control group (standard mean difference [SMD] = −1.09, 95% CI: −4.71 to 2.53, p = 0.556), although this difference was not statistically significant. The study indicates that liver cancer surgery patients with higher body mass index were at an increased risk of postoperative wound infection and complications. This finding highlights the importance of considering body mass index as a factor in the management and care of patients undergoing liver cancer surgery.